Dairy cattle damage in the arboreal component of a silvopastoral system - Brun, Eleandro José; Dalposso, David Marlon; Kuss, Fernando; Sartor, Laércio Ricardo; Brun, Flávia Gizele Konig; Peretiatko, Cláudia Dyana Santos (Revista Ecologia e Nutrição Florestal - ENFLO, 2017)
The study aimed to quantify the damage caused by dairy cattle on the growth and recovery capacity of hybrid Eucalyptus grandis x E. camaldulensis (grancam) trees in a experimental silvopastoral system implanted in October/2012, after release of animals in the area in winter/2014. The experimental design consisted of a two-factor scheme, considering the distance between the animals entering the area and the double planting lines (factor 1) and the two evaluation occasions (February / 2015 and July / 2016) (factor 2). The damage levels (low / medium / high) were classified and their interference on growth in diameter at breast height (DBH) and total height (Ht), as well as the recovery capacity of the trees were evaluated. There was no significant interaction between factor 1 and 2 for DBH. The trees of the lines closest to the place of entry of the animals in the area showed a lower DBH (19.7 and 20.6 cm) in relation to the furthest lines (26.1 and 23.9 cm). The interaction was significant for Ht, but not significant difference between the lines. At the two evaluations, there was a general average increase of 2.59 cm year-1 in DBH and, in Ht, of 5.9 and 6.0 m in year-1 in lines 2 and 4, 4.6 and 4.4 m year-1 in lines 1 and 3, respectively. In 2015, most of the trees presented high-level of damage (65%), falling to 6.7% in 2016, showing the recuperation capacity of grancam. There was a significant inverse correlation between DBH and Ht with high level of damage (r = -0.25 and -0.24, respectively), showing that small trees are more susceptible to damage by cattle.